Bilingual Program in Asctronomy Class at Islamic University - Nur Zahrah Azizah; Haryanto Atmowardoyo; Andi Anto Patak (Har Press Indonesia, 2021)
The research is based on the challenges associated with the implementation of the bilingual program in teaching astronomy class in particular. It focuses on the use of bilingual program in the teaching-learning activities and the responses of students to teaching-learning activities. This study employed a descriptive qualitative analysis approach. The researchers employ the descriptive approach to interpret the data which in the form of phrases. Furthermore, as the data are specified, assessed, interpreted, and extracted from it, the researchers use the qualitative technique. Events, informants, and records are the sources of the research data. The researchers employed observations and interviews to acquire the data as tools for data retrieval. The researchers use notes for the observation phase to see the application of the bilingual program. The interview was used to find the lecturer's bilingual class strategy and the answers of the students to the instructional activities. A lecturer and second-semester students from the Department of Astronomy were the subjects of this study. As the result of this research, the lecturer had applied the bilingual program in teaching astronomy students. Although the lecturer employ two languages in the materials, they are mindful about the demands and curricula of the students when choosing the teaching material. The researchers have revealed that bilingual students are able to apply this strategy in two languages and have a positive response so that it can be used by other lecturers or universities.